THE SIMILARITIES AND DIFFERENCES BETWEEN THE STRATEGIES OF ENGLISH-INDONESIAN TRANSLATION OF ENGLISH PARTICIPIAL CLAUSES IN SIDNEY SHELDON’S MORNING, NOON AND NIGHT AND JOHN GRISHAM’S THE STREET LAWYER - Menik Winiharti (Kajian Linguistik dan Sastra, 2011)
The participial construction is one that exists in English but not in Indonesian. With regard to the translation, it might not be easy to translate a text having a structure that exists in one language (as a source language/SL) but not in the other (as a target language/TL). This study analyses the English participial clauses and their Indonesian translations in terms of the strategies applied in the translation. It focuses on two types of participial clauses; they are adverbial clauses and adjectival clauses. The data evaluated are the texts in Sidney Sheldon’s novel Morning, Noon, and Night (1995) which is translated into Pagi, Siang dan Malam (1996) by Hendarto Setiadi and John Grisham’s novel The Street Lawyer (1998) which is translated into Pengacara Jalanan (1998) by Widya Kirana and Diniarty Pandia. This study compares the strategies that the translators apply and tries to find the similarities as well as differences in the strategies used in the translations of the two novels. To reach these objectives, the English version and the Indonesian translations are compared and analyzed to determine the strategies applied and to find the similarities and differences of the strategies.Keywords: participial clauses, translation, strategies, Source Language (SL), Target Language (TL), adverbial clauses, adjectival clauses